Pendampingan Penggunaan Slims (Senayan Library Management System) Dalam Upaya Revitalisasi Perpustakaan Sekolah Dasar - Arif Chasannudin; Khilda Alfiani Aqiliya; Ayyun Afroh; Ahmad Miftahus Syifa (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This community service program is the revitalization of the library at SDN Karanglegi 01 Trangkil Pati. The background to this activity is the poor condition of the school library so that its function is not optimal. This service method is ABCD (Asset Based Community Based) using 5D steps (Discovery, Dream, Design, Define, and Destiny). The parties involved in this service are lecturers, KKN students, teachers and students. This activity includes several things such as assistance in using the library information system and redesigning the library. The result of this activity was that the school succeeded in reorganizing the library using the SLiMS (Senayan Library Management System) information system. The servants conducted workshops for teachers about this system as well as accompanying them on installation and use. After that, improvements were made to the layout and reading material aspects. Layout by arranging bookcases, reading areas and beautifying the library. The number of reading materials was increased by borrowing via cross-leverage from PERPUSDA Pati and also open donations of reading books.